Children and adolescent consumer behavior: Insights from the life course paradigm - Moschis, George P.; Mathur, Anil (Journal of consumer behaviour, 2024)
Researchers have long been interested in understanding young consumers, but they have had inadequate methods for studying their consumption‐related thoughts and actions at early stages of life and how these develop and change during formative years. Recent theoretical and methodological advances in behavioral and social science have contributed to the development of a research approach, known as “life course paradigm.” This approach has helped replace and integrate previously used theories and methods by offering researchers an over‐arching multi‐theoretical framework for studying a wide variety of phenomena; and it has rapidly diffused across disciplines, and is increasingly used internationally. This article shows how consumer researchers could benefit from applying this conceptual research framework to improve existing models and study youths' consumer behavior in an innovative way.